Bacterial screening of platelet donations in England, 2014-2023 - Chugh, Vidushi; Secret, Shannah; Davison, Katy; John, Autumn St; Simmonds, Peter; Brailsford, Susan R.; Harvala, Heli (Wiley-Blackwell, 2026)
Background and Objectives
Bacterial contamination of blood components is an ongoing problem in transfusion medicine. We analysed the bacterial screening data of platelets from England, 2014–2023, and compared this with data on reported near-misses and transfusion-transmitted infections (TTIs).
Materials and Methods
Anonymized data on bacterial screening of pooled and apheresis platelet donations were reviewed, including the number of donations collected yearly, results from bacterial screening and time from sampling to detection. The findings were compared with data on near-misses and TTIs reported during the same period.
Results
Screening of 1249,513 apheresis and 1,495,707 pooled platelet donations identified bacterial contamination in 2949 donations, including 78 bacterial species. Over four-fold higher frequency of confirmed bacterial contamination was observed in pooled platelets compared to apheresis donations (0.09% [1096/1,249,513] vs. 0.02% [362/1,495,707], p < 0.0001). Rates of bacterial contamination of pooled platelet doubled during the study period. Staphylococcus aureus was the most commonly detected highly pathogenic bacterial contaminant (29/147, 19.7%; 15/29, 52% in apheresis platelets). It was also implicated in 1 confirmed case of bacterial TTI and in 8 of 10 reported bacterial near-miss cases.
Conclusion
Increasing frequencies of bacterial contamination, mostly related to skin flora, were noted in pooled platelets. Furthermore, S. aureus was notably associated with near-miss events. Our findings demonstrate a limitation of bacterial screening, with evidence of bacterial growth after platelets were likely supplied for clinical use.